PJMHS 2022
DOI: 10.53350/pjmhs22162237
|View full text |Cite
|
Sign up to set email alerts
|

A-Effects of Drugs on Spontaneous Contractions of Rabbit Jejunum

Abstract: Aim: To find out possible to determine effect of C. reflexa extract on spontaneous contractions of rabbit jejunum. Methods: Animal experimental in vitro study from 1st October 2017 to 30 September 2018 at Pharmacology experimental lab, Wah Medical College Wah Cantt. Study model was Isolated pieces of rabbit jejunum and ileum. Sampling Technique used was Simple Random. Tissue considered fit for experiment after initial equilibration and stabilization. Result: Three increasing concentrations (0.1mg/ml, 0.2mg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Pharmacological experiments have demonstrated that different extracts and pure compounds from this species exhibit a broad range of biological properties, including anti spasmodic effect on intestinal motility, antibacterial, antiin ammatory, antiviral, antioxidant, and antidiabetic activities [16]. Rabbit ileal tissue was selected for this experiment as it is considered more suitable for studying the response of agonist in the presence of antagonists [17]. Intestinal motility is mainly controlled by the enteric nervous system through multiple mediators, mainly acetylcholine, histamine, serotonin, bradykinins, dopamine etc.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological experiments have demonstrated that different extracts and pure compounds from this species exhibit a broad range of biological properties, including anti spasmodic effect on intestinal motility, antibacterial, antiin ammatory, antiviral, antioxidant, and antidiabetic activities [16]. Rabbit ileal tissue was selected for this experiment as it is considered more suitable for studying the response of agonist in the presence of antagonists [17]. Intestinal motility is mainly controlled by the enteric nervous system through multiple mediators, mainly acetylcholine, histamine, serotonin, bradykinins, dopamine etc.…”
Section: Discussionmentioning
confidence: 99%